Evaluation of the precision of some new global Earth Gravitational Models in the East Vietnam Sea - Do, Van Mong; Nguyen, Van Sang; Tran, Tuan Dung; Nguyen, Thanh Le; Khuong, Van Long; Nguyen , Dinh Hai; Tran , Manh Cuong; Nguyen, Trong Dai; Tran, Tuan Duong (Vietnam Journal of Marine Science and Technology, 2023)
This study is to evaluate the precision of some new global Earth Gravitational Models in the East Vietnam Sea, selecting the best model. The method and the program for calculating Free air gravity anomaly from the global earth gravitational model have been researched and developed. Evaluation of the precision of the models is done by comparing the models with ship-derived gravity anomalies. Data with anomalous signs are detected and removed when the deviation exceeds three times the root mean square deviation. The six global earth gravitational models were evaluated in the experimental section: EGM2008, EIGEN6-C4, GECO, SGG-UGM-1, XGM2019E, and SGG-UGM-2. The evaluation results show that: in the East Vietnam Sea, when compared with 35855 points of shipborne data, the above models respectively have standard deviations of: ±6.046 mGal, ±7.559 mGal, ±5.781 mGal, ±5.832 mGal, ±5.448 mGal, and ±5.236 mGal; all models have mean deviations from shipborne gravity anomalies of about +5 mGal; The correlation between the models and the shipborne data is quite good; The model SGG-UGM-2 has the highest precision. The Free air gravity anomalies from this model have also been calculated over the territorial waters of Vietnam in the form of a grid with a mesh size of 1’ × 1’.